Vascular Endothelial Growth Factor Inhibitor Therapy and Cardiovascular and Renal Damage in Renal Cell Carcinoma - Lai, Silvia; Molfino, Alessio; Seminara, Patrizia; Longo, Flavia; Innico, Georgie; Coppola, Bettina; Mastroluca, Daniela; Galani, Alessandro; Dimko, Mira; Aceto, Paola; Lai, Carlo (Current Vascular Pharmacology, 2018)
Background: Sunitinib, a tyrosine kinase inhibitor of vascular endothelial growth factor (VEGF), is approved for first and second line treatment of advanced renal cell carcinoma (RCC). Knowledge on the effects of sunitinib on cardiovascular (CV) risk and renal damage is limited. Aim: To evaluate possible renal and CV damage in patients with RCC treated with sunitinib. Materials and Methods: Patients with metastatic RCC treated with sunitinib were enrolled. This population was evaluated before starting treatment (T0) and after 3 months (T1). Laboratory and instrumental parameters, including interventricular septum (IVS) and left ventricular mass index (LVMI) were recorded before and after treatment. Results: Thirty-two patients (13 female, 19 male, mean age 62.7±9.9 years) were enrolled. We observed overtime, a significant reduction in estimated glomerular filtration rate (eGFR) (p=0.01), hemoglobin (Hb) (p=0.04) and 25-hydroxyvitamin D (25-OH-VitD) (p=0.002), in association with a significant increase in serum phosphorus (p<0.001), systolic blood pressure (SBP) (p<0.001), diastolic blood pressure (DBP) (p<0.001), IVS (p=0.03) and proteinuria (p<0.001), while we showed no significant differences in glycosuria, phosphaturia, serum uric acid, intact parathormone, and LVMI. Conclusion: We observed the development of renal damage and worsening of CV indices in patients treated with sunitinib. We suggest to consider a careful assessment of renal function and CV risk factors, before initiation and during administration of this drug.
Keywords: Sunitinib